(untitled) (Journal of Plant Disease Sciences, 2017)
A field experiment on effect of different levels of nitrogen and Gluconoacetobacter diazotrophicus was carried out on sugarcane (CO-86032) during 2015-16. inoculation and N-fertilizer application was not G. diazotrophicus found to increase significantly emergence percentage invarious treatments, whereas other growth parameters shoot length, root length and vigour index were found viz. significantly increased due to various treatments.Amongst all the treatments, 75% RDN + sett treatment has given maximum emergence percent G.diazotrophicus i.e. 86.67 per cent of sugarcane at 30 days after planting. Highest shoot length, root length and vigour index of sugarcane were recorded in treatment of 75% RDN + G.diazotrophicus G. diazotrophicus sett treatment. The treatment of 75 % RDN + (T ) sett treatment recorded highest population dynamics of i.e. 6 G. diazotrophicus 9.0 x10 cfu/gand highest nitrogen content in leaf i.e. 2.62 per cent at 120 days after 5 planting.